2020
DOI: 10.1038/s41598-020-57482-0
|View full text |Cite
|
Sign up to set email alerts
|

Components of partial resistance to Plasmopara viticola enable complete phenotypic characterization of grapevine varieties

Abstract: Six components of partial resistance (RCs) were studied in 15 grapevine varieties with partial resistance to Plasmopara viticola: (i) infection frequency (ifR, proportion of inoculation sites showing sporulation), (ii) latent period (LP50, degree-days between inoculation and appearance of 50% of the final number of sporulating lesions), (iii) lesion size (LS, area of single lesions in mm 2), (iv) production of sporangia (SpoR, number of sporangia produced per lesion, and SpoR', number of sporangia produced per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 62 publications
(70 reference statements)
4
43
2
Order By: Relevance
“…It is therefore possible that we used by chance, among the few available, an Rpv12 -carrier with a particularly favourable genetic background, although several reports converge on a consensus that, based on OIV452 scores, Rpv12 -dependent resistance is stronger across varieties than Rpv3 -dependent resistance 55 , 56 . Bove and Rossi 57 also showed that three varieties operating Rpv12 -dependent defence clustered together and separately from varieties carrying other Rpv genes for five defence components (i.e. proportion of inoculated sites that develop disease symptoms, length of the latent period, number of waves of sporangial release during the infectious period upon extended incubation of sporulating lesions, sporangial density per lesion, infectivity of the released sporangia), suggesting that the outcome of the defence response is still more dependent on the type of R-gene than on the genetic background of the variety.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that we used by chance, among the few available, an Rpv12 -carrier with a particularly favourable genetic background, although several reports converge on a consensus that, based on OIV452 scores, Rpv12 -dependent resistance is stronger across varieties than Rpv3 -dependent resistance 55 , 56 . Bove and Rossi 57 also showed that three varieties operating Rpv12 -dependent defence clustered together and separately from varieties carrying other Rpv genes for five defence components (i.e. proportion of inoculated sites that develop disease symptoms, length of the latent period, number of waves of sporangial release during the infectious period upon extended incubation of sporulating lesions, sporangial density per lesion, infectivity of the released sporangia), suggesting that the outcome of the defence response is still more dependent on the type of R-gene than on the genetic background of the variety.…”
Section: Discussionmentioning
confidence: 99%
“…Several crossing lines inbreed with American Vitis species are currently commercialized as partially resistant varieties to fungal pathogens, e.g. Regent, Calardis Blanc, Solaris 8,9 .…”
mentioning
confidence: 99%
“…So far, plant resistance is still only characterised during the epidemics, e.g. in grapevine (Bove & Rossi, 2020). However, pathogen life-cycle stages related to intercrop transmission, like the production of oospores in Plasmopara viticola, are starting to be evaluated (Delbac et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Host resistance is usually described by its impact on pathogen life history traits during the epidemic phase, by e.g. infection efficiency, latent period or sporulation (Bruns et al, 2012;Delmas et al, 2016;Dumartinet et al, 2020;Leclerc et al, 2019;Bove & Rossi 2020). In short, from an epidemiological point of view, qualitative host resistance reduces the number of compatible infections whereas quantitative host resistance reduces the amplification during the epidemics (Fig.…”
Section: Introductionmentioning
confidence: 99%